Perceptions of tsunami susceptibility and self-efficacy among adolescents in Indonesia: The influence of gender, religion, location, age, hazard information source, and past experience. (September 2022) - Hall, Sarah; Sloan-Aagard, Chantel; Harris, Ron; Emmett, Chad; Prasetyadi, Carolus; Pettersson, Jessica; Cope, Amelia; Hamson Cox, Mckelle
Abstract: Perceptions of tsunami susceptibility and self-efficacy among adolescents in Indonesia: The influence of gender, religion, location, age, hazard information source, and past experience. The densely populated Indonesian archipelago is highly vulnerable to earthquakes and tsunamis. Behavioral theory suggests perceived susceptibility and perceived self-efficacy are positively correlated with preventive behaviors. We surveyed adolescents (N = 2386) in tsunami-vulnerable coastal areas of Java, Bali, Lombok, and Sumba Indonesia. We conducted a stepwise logistic regression analysis of perceived tsunami susceptibility and self-efficacy. Explanatory variables included sex, age, religion, island of residence, hazard information source, previous participation in tsunami evacuation drills, and personal tsunami experience. The majority (60.6%) of participants believed that they were susceptible to an earthquake. About half of participants believed they were susceptible to a tsunami (49.8%) and that they would be able to save themselves if a tsunami occurred (48.5%). Individuals residing in Java, females, Muslims, older participants, and those who received tsunami information from the Internet and Indonesia's regional governmental disaster management agency (BPBD) were significantly more likely to feel susceptible to a tsunami. Catholics, Protestants, individuals living in Java, those who participated in past tsunami evacuation drills, and those with personal tsunami experience had significantly higher perceived self-efficacy. Females and participants who received hazard-related information from the Internet and BPBD had significantly lower perceived self-efficacy. Our study highlights the importance of providing culturally competent information about local tsunami risk to vulnerable locations through a variety of communication channels. Identifying cultural, economic, and religious barriers is important when developing educational interventions. Efficacy perceptions should be improved through education about immediate self-evacuation after observation of tsunami natural warning signs, construction of vertical evacuation structures in coastal areas, and encouraging participation in tsunami evacuation drills.